Increased Dopamine Type 2 Gene Expression in the Dorsal Striatum in Individuals With Autism Spectrum Disorder Suggests Alterations in Indirect Pathway Signaling and Circuitry - Brandenburg, Cheryl; Soghomonian, Jean-Jacques; Zhang, Kunzhong; Sulkaj, Ina; Randolph, Brianna; Kachadoorian, Marissa; Blatt, Gene J. (Frontiers in Cellular Neuroscience, 2020)
Autism spectrum disorder (ASD) is behaviorally defined and diagnosed by delayed and/or impeded language, stereotyped repetitive behaviors and difficulties with social interactions. Additionally, there are disruptions in motor processing, which includes the intent to execute movements, interrupted/inhibited action chain sequences, impaired execution of speech and repetitive motor behaviors. Cortical loops through basal ganglia (BG) structures are known to play critical roles in the typical functioning of these actions. Specifically, corticostriate projections to the dorsal striatum (caudate and putamen) convey abundant input from motor, cognitive and limbic cortices and subsequently project to other BG structures. Excitatory dopamine (DA) type 1 receptors are predominantly expressed on GABAergic medium spiny neurons (MSNs) in the dorsal striatum as part of the “direct pathway” to GPi and SNpr whereas inhibitory DA type 2 receptors are predominantly expressed on MSNs that primarily project to GPe. This study aimed to better understand how this circuitry may be altered in ASD, especially with regard to the neurochemical modulation of GABAergic MSNs within the two major BG pathways. We utilized two classical methods to analyze the postmortem BG in ASD in comparison to neurotypical cases: ligand binding autoradiography to quantify densities of GABA-A, GABA-B, 5-HT2 and DA type 1 and 2 receptors and in situ hybridization histochemistry (ISHH) to quantify mRNA for D1, D2 receptors and three key GABAergic subunits (alpha1, beta2, gamma2), as well as the GABA synthesizing enzymes (GAD65/67). Results demonstrated significant increases in D2 mRNA within MSNs in both the caudate and putamen, which was further verified by proenkephalin mRNA that is co-expressed with the D2 receptor in indirect pathway MSNs. In contrast, all other GABAergic, serotonergic and dopaminergic markers in the dorsal striatum had comparable labeling densities. These results indicate alterations in the indirect pathway of the BG, with possible implications for the execution of competing motor programs and E/I imbalance in the direct/indirect motor feedback pathways through thalamic and motor cortical areas. Results also provide insights regarding the efficacy of FDA approved drugs used to treat individuals with ASD acting on specific DA and 5-HT receptor subtypes.